2020
DOI: 10.1038/s41467-020-20080-9
|View full text |Cite
|
Sign up to set email alerts
|

Pontin arginine methylation by CARM1 is crucial for epigenetic regulation of autophagy

Abstract: Autophagy is a catabolic process through which cytoplasmic components are degraded and recycled in response to various stresses including starvation. Recently, transcriptional and epigenetic regulations of autophagy have emerged as essential mechanisms for maintaining homeostasis. Here, we identify that coactivator-associated arginine methyltransferase 1 (CARM1) methylates Pontin chromatin-remodeling factor under glucose starvation, and methylated Pontin binds Forkhead Box O 3a (FOXO3a). Genome-wide analyses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…This results in aberrant development of heart ischemia-sensitive phenotype in offspring [ 75 ]. Arginine methylation is an epigenetic modification involved in autophagy and is catalyzed by the protein arginine methyltransferase (PRMT) family [ 76 ]. In this study, the authors mention that coactivator-associated arginine methyltransferase 1 (CARM1) methylates Pontin chromatin-remodeling factor under glucose starvation and interacts with FoxO3, a transcription factor for transcriptional activation of autophagy genes [ 76 ].…”
Section: Epigenetic Regulation Of Autophagymentioning
confidence: 99%
“…This results in aberrant development of heart ischemia-sensitive phenotype in offspring [ 75 ]. Arginine methylation is an epigenetic modification involved in autophagy and is catalyzed by the protein arginine methyltransferase (PRMT) family [ 76 ]. In this study, the authors mention that coactivator-associated arginine methyltransferase 1 (CARM1) methylates Pontin chromatin-remodeling factor under glucose starvation and interacts with FoxO3, a transcription factor for transcriptional activation of autophagy genes [ 76 ].…”
Section: Epigenetic Regulation Of Autophagymentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 ) δ 8.31 (s, 1H), 8.28 (m,, 1H), 7.38−7.43 (m, 2H), 4.55 (d, J = 7.1 Hz, 1H), 4.52−4.43 (m, 1H), 4.08 (dd, J = 8.1, 2.7 Hz, 2H), 3.87 (s, 2H), 3.79 (s, 3H), 3.67 (dd, J = 11.5, 9.9 Hz, 2H), 2.81− 2.76 (m, 2H), 2.73− 2.66 (m, 2H), 2.41 (s, 3H), 2.25 (s, 3H), 2.22 (s, 3H), 2.21 (dd, J = 12.5, 2.2 Hz, 2H), 2.00 (s, 3H), 1.69 (qd, J = 11.9, 4.4 Hz, 2H). 13 (23). The title compound was obtained as a colorless oil in 25% yield from 57a using a method similar to that described for compound 9.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…15,16 Considering these biological characteristics, CARM1 contributes to diverse cellular processes including RNA splicing, 17,18 transcriptional coactivation, 19 DNA repair, 20 cell differentiation, 21 and autophagy. 22,23 Accumulated evidence suggests the essential roles of CARM1 in both hematologic neoplasms like acute myeloid leukemia 24 and solid cancers including breast, 25 lung, 26 liver, 27 prostate 28 and colorectal carcinoma, 29 and overexpressed CARM1 is correlated with poor patient prognosis. 30,31 Pharmacological inhibition and genetic depletion of CARM1 can cause antiproliferation effects in specific cancer cell lines, 8,15,24,26 indicating that targeting CARM1 may be an effective therapeutic strategy for cancer treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…PRMT4 induces autophagy-related protein degradation by mediating FoxO3 activity. In support of this notion, recent studies in non-muscle cells have shown that PRMT4-dependent histone arginine methylation is an essential nuclear regulation to induce autophagy after nutrient starvation ( Shin et al, 2016 ; Yu et al, 2020 ). Although the phenotype studies suggest an opposing role of PRMT1 and PRMT4 in the control of autophagy, the functional interaction between PRMT1 and PRMT4 in muscle homeostasis and plasticity is currently unclear.…”
Section: Protein Arginine Methyltransferasesmentioning
confidence: 88%